Exploitation’s grounding problem - Ferguson, Benjamin (Economics and philosophy, 2025)
Standard accounts of what makes exploitation wrong ground its wrong in distributive unfairness: when A exploits B he wrongs her by taking a greater share of the benefits from their interaction than he ought. I argue that this standard account does not succeed; distributive unfairness is neither the sole, nor the primary wrong of exploitation. I assume that distributive unfairness is pro tanto wrong. However, I argue that in situations where transactors’ consent to a transaction is morally valid, it is also morally transformative and overrides distributive unfairness’s pro tanto wrong. Thus, wrongful exploitation requires morally invalid consent.